Fulgoroidea types (Hemiptera-Fulgoromorpha) housed at the Museo de La Plata entomological collection (Argentina) - Lenicov, Ana M. Marino De Remes; Maciá, Arnaldo; Mariani, Roxana; Pereyra, Mora (Zootaxa, 2026)
A catalog of the 44 primary types and 340 secondary types specimens of Fulgoroidea housed in the collection of the Entomology Division of the Museo de La Plata is presented. This collection represents 43 nominal species currently classified in 8 families and 26 genera. According to our survey, the types of Euides fucata Berg, 1883, Delphacodes collaris Remes Lenicov & Tesón, 1987 and Delphacodes variablis Remes Lenicov & Tesón, 1987 are missing in the collection. Label data, descriptions of the state of preservation of specimens, and taxonomic remarks are given. Photographs of most of the type specimens are also included.